Long-term lime and phosphogypsum broadcast affects phosphorus cycling in a tropical Oxisol cultivated with soybean under no-till - Firmano, Ruan Francisco; Colzato, Marina; Bossolani, João William [UNESP]; Colnago, Luiz Alberto; Martin-Neto, Ladislau; Alleoni, Luís Reynaldo Ferracciú (Springer Nature, 2021)
Broadcast application of lime or phosphogypsum to suppress aluminum (Al) in soils can influence chemistry and fate of phosphorus (P) in natural environments. However, the long-term effects of these amendments in organic P (Po) forms and in soil biochemical properties remain unclear. This study assessed the effect of lime and phosphogypsum management on Po contents, soil biochemical properties, and soybean (Glycine max L.) nutrition and yield. The long-term field experiment was carried out in highly weathered soil under no-till in southeastern Brazil. Soil chemical properties commonly used in soil fertility assessments were severely influenced by Al-suppressors broadcast over time. Changes in soil chemical attributes affected nutrient concentrations in soybean index leaves and grain yield, which was higher when lime was associated to phosphogypsum. The presence of Al-suppressors in the soil influenced the activity of enzymes linked to P and carbon (C) cycles, mainly in the 0–20 cm layer. The pH was mostly influenced by the activity of phosphatases, especially in the limed soil. Myo-inositol hexakisphosphate (IHP6) was the second most abundant P form in the soil after orthophosphates, indicating crop litter P-inputs regulate the Po cycle. Over time, soil management influenced the diversity and abundance of Po forms measured by 31P nuclear magnetic resonance (NMR) spectroscopy compared to soil under native vegetation. Differences were most significant for the proportions of deoxyribonucleic acid (DNA), myo- and scyllo-inositol hexakisphosphates, and α- and β-glycerophosphates, which were higher in the soil under native vegetation.
Keywords: 31P NMR spectroscopy; Inositol phosphates; Phosphatases; Soil acidity; Tropical soil